2021
DOI: 10.1002/pmrj.12700
|View full text |Cite
|
Sign up to set email alerts
|

The effect of first‐time 4‐wheeled walker use on the gait of younger and older adults

Abstract: The effect of first-time 4-wheeled walker use on the gait of younger and older adults ABSTRACT Introduction: The 4-wheeled walker is intended to enhance balance and gait for older adults.Yet, some research suggests that walking aids increase falls risk. An understanding of the influence of age with walker use on gait performance is required.Objective: To examine the effect of initial 4-wheeled walker use on spatiotemporal gait parameters between younger and older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…They also reduce the load on the lower limbs, thereby enhancing balance [ 8 ]. Studies have reported that elderly people felt more stable and safer when using walking aids [ 11 , 12 ]. Walking aids can help individuals maintain or regain social activity and improve their confidence and sense of security [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…They also reduce the load on the lower limbs, thereby enhancing balance [ 8 ]. Studies have reported that elderly people felt more stable and safer when using walking aids [ 11 , 12 ]. Walking aids can help individuals maintain or regain social activity and improve their confidence and sense of security [ 13 ].…”
Section: Introductionmentioning
confidence: 99%